Oportunidades sociais e o Programa Jovem Aprendiz: uma análise à luz do pensamento de Amartya Sen - Silva, Flávio Alves da (Universidade Federal do Tocantins, 2016)
This research analyzes the access to social opportunities for young participants of the "Young Apprentice Program" held at SENAI-TO and seeks to ascertain to what extent the Young Apprentice Program promotes access and expansion of social opportunities to its beneficiaries during program execution. This is sought through a descriptive exploratory study, in which priority was given to the speeches of subjects learners who experience the program. Data collection used bibliographic and documentary research and the application of questionnaires with semi-open and open questions, with all members apprentices Programme in SENAI-TO Palmas Unit. Data analysis was performed using the Content Analysis (BARDIN, 2011), in his "theme" mode. The results consider that in general the program can be classified to the level of "medium high" in promoting access to social opportunities, but this classification is not unanimous in all categories surveyed. The promotion of such access has different variations of degree of occurrence ranging from the very high degree to the very low level of presence and / contribution. Given the results, you can infer that the PJA is a program that promotes access to social opportunity and helps to develop and enhance the skills necessary to access the goods necessary for survival and lead the life they consider worth living. Also plays / develops an instrumental role in expanding capacity in generating social change. As can be seen as contributing in the promotion and expansion of instrumental freedoms that constitute and promote human development, which is to SEN (2010), the key factor for the development of a nation.